Molecular Insight Into the IRE1α-Mediated Type I Interferon Response Induced by Proteasome Impairment in Myeloid Cells of the Brain - Studencka-Turski, Maja; Çetin, Gonca; Junker, Heike; Ebstein, Frédéric; Krüger, Elke (Frontiers in Immunology, 2019)
Proteostasis is critical for cells to maintain the balance between protein synthesis, quality control and degradation. This is particularly important for myeloid cells of the central nervous system (CNS) as their immunological function relies on proper intracellular protein turnover by the ubiquitin-proteasome system (UPS). Accordingly, disruption of proteasome activity due to i.e. loss-of-function mutations within genes encoding proteasome subunits results in systemic autoinflammation. On the molecular level, pharmacological inhibition of proteasome results in endoplasmic reticulum (ER) stress-activated unfolded protein response (UPR) as well as an induction of type I interferons (IFN). Nevertheless, our understanding as to whether and to which extent UPR signaling regulates type I IFN response is limited. To address this issue, we have tested the effects of proteasome dysfunction upon treatment with proteasome inhibitors in primary murine microglia and microglia-like cell line BV-2. Our data show that proteasome impairment by bortezomib is a stimulus that activates all three intracellular ER-stress transducers activation transcription factor 6 (ATF6), protein kinase R-like endoplasmic reticulum kinase (PERK) and inositol requiring protein 1 alpha (IRE1α), causing a full activation of the UPR. We further demonstrate that impaired proteasome activity in microglia cells triggers an induction of IFNβ1 in an IRE1-dependent manner. An inhibition of the IRE1 endoribonuclease activity significantly attenuates TANK-binding kinase 1 (TBK1)-mediated activation of type I IFN. Moreover, interfering with TBK1 activity also compromised the expression of C/EBP homologous protein 10 (CHOP), thereby emphasizing a multilayered interplay between UPR and type IFN response pathway. Interestingly, the induced PERK-ATF4-CHOP and IRE1-XBP1s axes caused a significant up-regulation of proinflammatory cytokine IL-6 expression that exacerbates STAT1/ STAT3 signaling in cells with dysfunctional proteasomes. Altogether these findings indicate that proteasome impairment disrupts ER homeostasis and triggers a complex interchange between ER-stress sensors and type I IFN signaling, thus inducing in myeloid cells a state of chronic inflammation.